ENHANCING AND IMPACTING OF THE INFOGRAPHICS POTENTIAL AS A PART OF DIRECTED ACTIVITIES RELATED TO MULTICODE TEXTS - Budnik, Ekaterina; Kuvaeva, Alena; Leshutina, Irina; Naumenko, Yulia; Vokhmina, Liliya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article presents the description of the linguo-didactic potential of infographics as one of the leading visual aids in teaching Russian as a foreign language at the present time. Infogaphics must be considered a paralinguistic tool which externally styles a text, pragmatically affects a recipient and performs some didactic functions within an educational text (informing, semantizing, stimulating utterance, controlling and facilitating the reconstruction of communication situations). The article gives the observation of different references which help to realize the nature of infographics and the principles of their creation. The authors also present their own teaching material with infographics which can be used in a foreign audience: it is based on “Directed Activities Related to Text” method as it forces students to interact with the text, use their background knowledge and thinking. The material includes tasks which promote the activation of language and speech skills of foreign students. It was approbated in the Russian language course within "Foreign language" discipline at the Philological faculty at Pushkin State Russian Language Institute during 2018-2019/2019-2020 academic years: 3-year students of baccalaureate (students from Southeast Asia).